Advances in research on the effects of medicinal and edible substances on lung cancer: an updated review - Yang, Ying; Jiang, Lingli; Li, Ke; Zhang, Genming; Wang, Junpeng; Li, Daorui (Frontiers in Pharmacology, 2026)
Lung cancer, as one of the malignant tumors with the highest morbidity and mortality worldwide, poses a serious threat to human life and health. Despite the fact that there have been significant advances in the modern medicine treatment of lung cancer, the problem of drug resistance and the potential toxic side effects associated with the respective treatment still restrict the clinical efficacy and the amelioration of patients’quality of life. Based on this background, the therapeutic value of traditional Chinese medicine (TCM) as an adjuvant has become increasingly prominent. Among these, medicinal and edible substances have garnered growing research attention for the adjuvant treatment of lung cancer, owing to their wide sources, fewer side effects, and multi-pathway anti-tumor potential. Medicinal and edible substances abound with polysaccharides, flavonoids, terpenoids, saponins, polyphenols, and other bioactive substances. They are pivotal in the prevention and treatment of lung cancer through multiple mechanisms, including anti-inflammatory effects, antioxidant effects, immunomodulation effects, inhibition of tumor angiogenesis effects, and cell regulation effects. In this review, the pharmacological action of active components in medicinal and edible substances and the mechanism of action in the treatment of lung cancer were reviewed systematically, and the research direction of medicinal and edible substances in the field of lung cancer in the future was prospected, in an effort to provide theoretical reference for promoting its in-depth application in the comprehensive treatment of tumors, as well as for its complementarity of strengths and coordinated advancement with modern medicine.